Flourishing Through Music Creation: A Qualitative Investigation of the Lullaby Project Among Refugee and Incarcerated Communities - Ascenso, Sara (Frontiers in Psychology, 2021)
The Lullaby Project is an innovative model developed to promote psychosocial change with vulnerable groups through community-based music creation. It pairs ex¬pectant and new mothers with professional musicians, to create a lullaby for their children. This paper presents an investigation of the project’s pilot implementation in the UK, bringing together musicians from the Royal Philharmonic Orchestra, refugee mothers and inmate fathers from a central London prison. The research aimed to under¬stand how the Lullaby Project was experienced, focusing on the potential areas of perceived change linked with the concept of mental health as flourishing. Participants (N=12) took part in semi-structured interviews and kept daily notes to aid recollection of the sessions in the interviews. Interpretative Phenomenological Analysis (IPA) was adopted as the research approach. Participants considered the project to carry significance for them in three key areas: i. wellbeing, through a strong sense of accom¬plishment, meaning and connectedness, and the experience of positive emotions; ii. proactivity, promoting initiative, both musical and relational and iii. reflectiveness, stimulating perspective-taking and positive coping mechanisms. The Lullaby Project offers an effective model towards promotion of flourishing among vulnerable groups, and the results make a strong case for its implementa¬tion.